Gut Microbiota Dysbiosis Is a Crucial Player for the Poor Outcomes for COVID-19 in Elderly, Diabetic and Hypertensive Patients - Magalhães, Nathalia Santos; Savino, Wilson; Silva, Patrícia Machado Rodrigues; Martins, Marco Aurélio; Carvalho, Vinicius Frias (Frontiers in Medicine, 2021)
A new infectious disease, named COVID-19, caused by the coronavirus associated to severe acute respiratory syndrome (SARS-CoV-2) has become pandemic in 2020. The three most common pre-existing comorbidities associated with COVID-19-related death are elderly, diabetic, and hypertensive people. A common factor among these risk groups for the outcome of death in patients infected with SARS-CoV-2 is dysbiosis, with an increase in the proportion of bacteria with a pro-inflammatory profile. Due to this dysbiosis, elderly, diabetic, and hypertensive people present a higher propensity to mount an inflammatory environment in the gut with poor immune editing, culminating in a weakness of the intestinal permeability barrier and high bacterial product translocation to the bloodstream. This scenario culminates in a low-grade, persistent, and systemic inflammation. In this context, we propose here that high circulating levels of bacterial products, like lipopolysaccharide (LPS), can potentiate the SARS-CoV-2-induced cytokines, including IL-6, being crucial for development of the cytokine storm in the severe form of the disease. A better understanding on the possible correlation between gut dysbiosis and poor outcomes observed in elderly, diabetic, and hypertensive people can be useful for the development of new therapeutic strategies based on modulation of the gut microbiota.